The genus Philoctetes Abeille de Perrin, 1879 from China, with description of two new species (Hymenoptera, Chrysididae) - Rosa, Paolo; Wei, Na-Sen; Notton, David; Xu, Zai-Fu (Zootaxa, 2015)
The Chinese species of the genus Philoctetes Abeille de Perrin, 1879 are revised and keyed for the first time. Six species are recorded, of which two are new for science: Philoctetes longiflagellis Rosa, Wei & Xu, sp. nov. (Inner Mongolia and Shanxi) and P. simulator Rosa, Notton & Xu, sp. nov. (Tianjin). The new synonym, Philoctetes cupratus (Mócsary, 1914), syn. nov. of Philoctetes mongolicus (du Buysson, 1901), is proposed. Philoctetes mongolicus (du Buysson, 1901) is newly recorded from Pakistan.